1980
DOI: 10.1042/cs059435s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Therapy on Left Ventricular Function in Hypertension

Abstract: 1. Twelve untreated hypertensive patients whose blood pressure was 171.8 +/- 5.5 mmHg systolic and 119.7 +/- 3.4 mmHg diastolic (mean +/- SEM) were treated aggressively with diuretics plus other antihypertensive agents. Echocardiograms were performed before, and 2 weeks, 3 months and 6 months after therapy. Blood pressures were lowered to an average of 142/98 mmHg over the 6 month period. 2. Mean velocity of circumferential fibre shortening rose from 1.1 +/- 0.09 to 1.3 +/- 0.06 diameters/s at 2 weeks and rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 12 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Echocardiographic studies have not shown a decrease in systolic function with LV mass reduction [11]. Also, midwall fractional shortening as a method of assessing myocardial contractibility did not show adverse effects on systolic function with reduction in LV mass [12].…”
Section: Risks Associated With Left Ventricle Hypertrophy Reductionmentioning
confidence: 98%
“…Echocardiographic studies have not shown a decrease in systolic function with LV mass reduction [11]. Also, midwall fractional shortening as a method of assessing myocardial contractibility did not show adverse effects on systolic function with reduction in LV mass [12].…”
Section: Risks Associated With Left Ventricle Hypertrophy Reductionmentioning
confidence: 98%
“…It is well known that angiotensin II impairs myocardial relaxation, [163] therefore, inhibition of angiotensin II may be expected to improve left ventricular filling. [115,169] However, it has to be considered that in these trials left ventricular filling was normal at baseline, thus, left ventricular filling would not be expected to improve.…”
Section: Effects On Diastolic Functionmentioning
confidence: 99%